Strukturelemente der Stadt Teheran und das Modell der modernen orientalischen Stadt - Seger, Martin (ERDKUNDE, 1975)
The eccentric position of the city of Teheran in a narrow oasis strip between high mountains and semi-desert was only fixed by the first western-type installations. The true period of renewal and broad western influence was the inter-war period under Reza Shah. The oil riches and strategic position of the country led later to integration in the western system and a stronger adoption of technological civilisation. This is most clearly expressed in the modern part of Teheran. The traditional centre of the oriental city, the bazaar quarter, stands in contrast to the prospering western-urban shopping centre. The bazaar too is expanding in the growing city even if it is losing higher order functions to the new upper-class centre. The duality of modern and traditional elements and the consequent growing apart of the city, make it seem profitable to develop a model of the new oriental city using Teheran as the example. The free development of the city has led to interesting differentiation based on socio economic laws: the double centres serve subsidiary and growing residential areas of differing quality. Social segregation leads to sharp isolation of the upper class quarter, whose direction of growth follows the more climatically favoured areas. The conceptual basis of the model is the division of society into a traditional population and a section of the population living according to western norms.